Strategi Komunikasi Start Up Laelyind dalam Meningkatan Brand Image dan Daya Saing - Rufaida Hanum; Erman Anom; Iswadi Iswadi (Journal of Management and Bussines (JOMB), 2023)
Brand Image is something that every company must pay attention to and always improve. This is very important because it will help maintain the existence and strengthen the competitiveness of the Company amidst ongoing business competence. Brand image also has a big impact on increasing sales of products released by each company. This research focuses on examining the strategies used by the fashion brand LaelyInd, a new start-up company in an effort to improve the brand image and competitiveness of the products it launches. The method used in this research is qualitative with a case study type. The data collection techniques used were interviews, observation and documentation. Based on research conducted, it is known that LaelyInd uses several important strategies in building the image of their products. One of them is effective promotional media as well as marketing mix business communication. Apart from that, the marketing team and other employees also collaborate in cultural events and fashion shows to improve brand image and product competitiveness. In an effort to achieve maximum public trust, LaelyInd always ensures the quality of the products they launch using premium and homemade materials. Keywords: Brand Image, Competitiveness, Communication Strategy, Start-Up